Randomized controlled trial on healthy volunteers of pharmacokinetic and antimicrobial activity of a novel hydrogel-containing chlorhexidine dressing to prevent catheter-related bloodstream infection - Masferrer, Emili; Riera-Rodríguez, Laura; Farré-Alins, Víctor; Vilà de Muga, Sandra; Arroyo-Muñoz, Francisco-Javier; González-Caro, María-Dolores (Frontiers in Medicine, 2024)
Introduction Catheter-related blood stream infection (CRBSI) is one of the most relevant complications associated to the use of intravascular catheters. In this context, chlorhexidine gluconate (CHG) releasing dressings have been developed to reduce the catheter colonization rate and the risk of infection. The aim of this study is to analyze the release rate of CHG and the antimicrobial activity of a novel CHG-releasing dressing, Oper film® protect CHG, and to compare these parameters to those of the dressing Tegaderm™ CHG in healthy volunteers. Methods The study was performed in a cohort of 25 healthy volunteers. Two commercially available chlorhexidine-containing dressings were evaluated and compared in this study, Oper film® protect CHG and Tegaderm™ CHG. The release of CHG and the antimicrobial capacity was determined for one week. Results HPLC analysis revealed that both dressings have an equivalent CHG release to the skin 2 days (Oper film® protect CHG, 321 μg/cm2; Tegaderm™ CHG, 279 μg/cm2) and 7 days (Oper film® protect CHG, 456 μg/cm2; Tegaderm™ CHG, 381 μg/cm2) after the placement of the products in the non-disinfected back of the subjects. On the other hand, Oper film® protect CHG and Tegaderm™ CHG similarly reduced colony forming units (CFU) in cultures obtained from the skin under the CHG-containing hydrogel compared to control cultures at both 2 days (control, 3.34 log10 cfu/cm2; Oper film® protect CHG, 0.64 log10 cfu/cm2; Tegaderm™ CHG, 0.7 log10 cfu/cm2) and 7 days (control, 3.95 log10 cfu/cm2; Oper film® protect CHG, 0.11 log10 cfu/cm2; Tegaderm™ CHG, 1 log10 cfu/cm2). Discussion Data confirm that the recent commercially available dressing Oper film® protect CHG maintains the release of CHG and the antimicrobial activity during at least 7 days, and possesses equivalent drug release and antimicrobial action to Tegaderm™ CHG.